2019
DOI: 10.1002/nop2.412
|View full text |Cite
|
Sign up to set email alerts
|

Relationship between spiritual health and hope by dietary adherence in haemodialysis patients in 2018

Abstract: Aim The present study aimed to determine the relationship between spiritual well‐being and hope through adherence to diet in haemodialysis patients referred to the dialysis centre. Design This research was a cross‐sectional study of a descriptive‐analytical type conducted on 120 patients undergoing haemodialysis in a haemodialysis centre of a hospital affiliated to Dezful University of Medical Sciences using the census method. Method The data were collected using a questionnaire and through the laboratory info… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
13
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(14 citation statements)
references
References 32 publications
0
13
1
Order By: Relevance
“…34 However, a study on hope in hemodialysis patients demonstrated that most of the participants (62%) had high levels of hope. 35 The moderate level of hope in the present study might be due to fear from the future, unpleasant complications, or even death. Therefore, hemodialysis patients could not be expected to have high levels of hope.…”
Section: Discussionmentioning
confidence: 62%
See 2 more Smart Citations
“…34 However, a study on hope in hemodialysis patients demonstrated that most of the participants (62%) had high levels of hope. 35 The moderate level of hope in the present study might be due to fear from the future, unpleasant complications, or even death. Therefore, hemodialysis patients could not be expected to have high levels of hope.…”
Section: Discussionmentioning
confidence: 62%
“…Similarly, a prior study revealed that the mean score of spiritual well-being was 75.05 and at the moderate level among hemodialysis patients. 35 It was also found previously that Iranian hemodialysis patients had high levels of spiritual health. 33 Iranian Muslim people had strong spiritual beliefs and used spirituality to cope with chronic diseases.…”
Section: Discussionmentioning
confidence: 67%
See 1 more Smart Citation
“…This study found that as the spiritual well‐being of people with chronic illnesses increased, their adaptation to chronic illness also increased. There were studies in the reviewed literature that examined the effect of spiritual well‐being on adherence to treatment and healthy lifestyle behaviors 29,40 and it was reported that spiritual well‐being affected self‐esteem and self‐efficacy, and health‐related behaviors and beliefs, leading to the application of health‐related activities, such as medication adherence, adherence to diet, and treatment 9,3 . found that spiritual well‐being was associated with compliance to medication among outpatients with heart failure and 29 reported a significant relationship between spiritual health and hope and dietary adherence in hemodialysis patients.…”
Section: Discussionmentioning
confidence: 99%
“…There were studies in the reviewed literature that examined the effect of spiritual well‐being on adherence to treatment and healthy lifestyle behaviors 29,40 and it was reported that spiritual well‐being affected self‐esteem and self‐efficacy, and health‐related behaviors and beliefs, leading to the application of health‐related activities, such as medication adherence, adherence to diet, and treatment 9,3 . found that spiritual well‐being was associated with compliance to medication among outpatients with heart failure and 29 reported a significant relationship between spiritual health and hope and dietary adherence in hemodialysis patients. Another study reported that spiritual well‐being increased the self‐management of chronic illnesses 21 and 41 reported that people with a higher spiritual well‐being had positive expectations, because they believed in a powerful God that met people's needs.…”
Section: Discussionmentioning
confidence: 99%